(untitled) (Research, Society and Development, 2025)
Tuberculosis (TB) is an infection caused by the bacteria Mycobacterium tuberculosis, which mainly affects the lungs and is transmitted through oral secretions. The disease, although often asymptomatic, is indicated by a persistent cough. Historically, TB dates back to ancient civilizations and arrived in Brazil with colonization. The disease continues to be one of the main causes of death from bacterial infections in the world and its situation has been worsened by the COVID-19 pandemic and social vulnerability. The research aimed to analyze factors that support the high prevalence of tuberculosis in the northern region of Brazil. The study in the North of Brazil analyzed TB records from 2015 to 2020, using data from DataSUS. The research was quantitative and identified factors such as diabetes, smoking, alcoholism and age group, correlating them with the prevalence of the disease. It was shown that Brazil registered 540,370 cases, with 2019 standing out for the highest number of infections. In the North region, Pará had the highest number of cases, while Amazonas had the highest prevalence rate. Factors such as smoking and alcoholism were shown to be the main risks for the development of TB, with a higher incidence among men and people aged 25 to 34 years. The study reinforces the high prevalence of the disease in the North region and the urgent need for control and prevention measures, highlighting tuberculosis as a serious public health problem in Brazil.